Ultrasound-Guided Peripheral Intravenous Access in the Emergency Department: Patient-Centered Survey - Keith Boniface; Hamid Shokoohi; Elizabeth M Schoenfeld (Western Journal of Emergency Medicine, 2011)
Introduction: To assess characteristics, satisfaction, and disposition of emergency department (ED) patients who successfully received ultrasound (US)-guided peripheral intravenous (IV) access. Methods: This is a prospective observational study among ED patients who successfully received US-guided peripheral IV access by ED technicians. Nineteen ED technicians were taught to use US guidance to obtain IV access. Training sessions consisted of didactic instruction and hands-on practice. The US guidance for IV access was limited to patients with difficult access. After successfully receiving an US-guided peripheral IV, patients were approached by research assistants who administered a 10-question survey. Disposition information was collected after the conclusion of the ED visit by accessing patients’ electronic medical record. Results: In total, 146 surveys were completed in patients successfully receiving US-guided IVs. Patients reported an average satisfaction with the procedure of 9.2 of 10. Forty-two percent of patients had a body mass index (BMI) of greater than 30, and 17.8% had a BMI of more than 35. Sixty-two percent reported a history of central venous catheter placement. This patient population averaged 3 ED visits per year in the past year. Fifty-three percent of the patients were admitted. Conclusion: Patients requiring US-guided IVs in our ED are discharged home at the conclusion of their ED visit about half of the time. These patients reported high rates of both difficult IV access and central venous catheter placement in the past. Patient satisfaction with US-guided IVs was very high. These data support the continued use of US-guided peripheral IVs in this patient population. [West J Emerg Med. 2011;12(4):475–477.]